Preparation of Phosphorescent Eu2+, Dy3+‐Doped Strontium Aluminate Nanoparticles by Laser Vaporization for the Modification of Therapeutic Contact Lenses. Issue 10 (19th June 2022) - Häusler, Jan; Müller, Frank A.; Müller, Lenka; Grabow, Janet; Cleve, Carla; Lotz, Christian; Röschlau, Mona; Bittorf, Patrick; Fromme, Roland; Kiebert, Ingrid; Grüne, Michelle; Schweizer, Stefan; et al.
Abstract : Biologically, effectively regulated light with a wavelength of about 485 nm can support physiological processes in the body and has a positive impact on the human sleep–wake rhythm. However, the application of common light therapy devices is not always practicable and sometimes difficult to integrate into everyday life. Here, miniaturization of therapy devices, for example, in the form of contact lenses, can reduce the handling disadvantages. Especially, contact lenses modified with phosphorescence materials offer this benefit. Herein, a method to prepare phosphorescent Eu 2+, Dy 3+ ‐doped strontium aluminate nanoparticles (NPs) by laser vaporization of macroscopic Eu 2+, Dy 3+ ‐doped Sr4 Al14 O25 particle powder and their integration into polymer‐based contact lenses is provided. NPs with a diameter of about 34 nm emit light in the desired therapeutic wavelength region. These novel NPs are biocompatible and do not show any negative effects during the testing of eye irritation safety in a 3D in vitro cornea model. Abstract : Phosphorescent lanthanide‐doped strontium aluminate nanoparticles (NPs) are prepared by laser vaporization of a macroscopic powder and integrated into contact lenses to apply for the light therapy of winter depression or sleep disorders. Novel NPs are biocompatible and do not show any negative effects during the testing of eye irritation safety in a 3D in vitro cornea model.